How to reduce vaccination hesitancy? The relevance of evidence and its communicator - Jens Eger; Lennart Kaplan; Henrike Sternberg (University of Göttingen, Department of Economics, 2022)
While the world faces unprecedented COVID-19 case numbers, vaccination rates in many countries are stagnating. A differentiated understanding of the concerns of the unvaccinated population seems urgently needed to design successful communication strategies. We conducted an original survey experiment among 2,100 unvaccinated respondents from Germany where a substantial population share remains unvaccinated. Guided by the elaboration likelihood model, this paper has two objectives: First, it explores by means of a latent class analysis how unvaccinated individuals might be characterised by their attitudes towards COVID-19 vaccination. The results suggest three different subgroups: Vaccination opponents, sceptics and those receptive to be vaccinated. Second, we investigate to what extent (i) communicators (scientists/politicians) can employ (ii) varying types of evidence (none/anecdotal/statistical) to improve vaccination intentions across these subgroups. While vaccination opponents seem largely unreachable, sceptics value information by scientists, particularly if supported by anecdotal evidence. Receptives seem to instead value statistical evidence from politicians.
Keywords: D91; H12; I12; I18; 330; vaccination hesitancy; COVID-19; Elaboration Likelihood Model; Latent ClassAnalysis; Persuasive messaging; Evidence provision